Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan pada Petugas PPSU di Kelurahan Sunter Jaya: The Influence of Leadership Style and Work Discipline on Employee Performance in PPSU Officers in Sunter Jaya Village - Angga Bagus Prasetyo; Musthafa Kamil (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Employee performance is a decisive variable in determining organizational success within both the private and public sectors. Efforts to enhance performance constitute a continuous agenda to ensure that human resources operate in accordance with established standards. This study aims to analyze the influence of leadership style and work discipline on the performance of Public Infrastructure and Facilities Handling (PPSU) officers in Sunter Jaya Village. This research is a quantitative study employing descriptive and causal methods. The population consists of all PPSU officers in Sunter Jaya Village, with a final sample of 88 respondents determined through purposive sampling and outlier data cleaning. The research instrument used was a Likert-scale questionnaire. Data analysis techniques involved validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination, processed using IBM SPSS software. The results indicate that, partially, leadership style and work discipline each have a positive and significant effect on employee performance. Simultaneously, both variables also demonstrate a positive and significant influence on employee performance. These findings prove that improving leadership style and work discipline can effectively drive more optimal performance among PPSU officers.